PFDN6 contributes to colorectal cancer progression via transcriptional regulation - Ning Li; Jing Han; Lan Jiang; Lei Liu; Xiao Sun; Nan Zheng; Fenghua Xu; LingYang Kong; WenXiang Hui; Wenxin Han; ZhiFeng Xiao; DongFeng Chen (eGastroenterology)
Objective Colorectal cancer (CRC) is a common cancer worldwide. Although there are several treatments for cancer, the therapeutic effect on CRC remains unsatisfactory, and it is imperative to identify new therapeutic targets.Design Prefoldin (PFDN) is mainly used in the cytoskeleton assembly during the folding of actin and tubulin monomers. However, whether PFDN subunits are involved in regulating the development of CRC remains to be elucidated. In this study, molecular biology, cell culture, transcriptome sequencing and other experimental techniques, combined with bioinformatics, were used to verify the regulatory effects of PFDN6 on CRC.Results PFDN6 expression is elevated in patients with CRC and is closely associated with the development of CRC. Knockdown of PFDN6 reduced the tumour cell number, promoted apoptosis, and inhibited the migration and invasion of CRC cells in HCT-116 and RKO cell lines. Mechanistically, differentially expressed genes and related signalling pathways in RKO cells after PFDN6 knockdown were analysed by transcriptome sequencing.Conclusion PFDN6 was found to regulate the generation and development of CRC by targeting ZNF575. These results open new avenues for therapeutic interventions for patients with CRC.